Analysis on Marketing Ability and Financial Performance in Internet Company - Zhuofan Yang; Yong Shi (2015 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology (WI-IAT), 2015)
This paper measures marketing ability and financial performance and examines what cause the overall operations inefficiency based on the operational process decomposition. The empirical research on e-portal and e-commerce company show that e-portal company has better marketing ability while e-commerce firm has better financial performance. For e-commerce company, it is marketing ability conversion inefficiency to lead to the overall operations inefficiency. In contrast, for e-portal company, lower financial performance conversion efficiency causes the overall operations inefficiency.